DESAIN DAN PEMBUATAN ALAT UKUR MEDAN MAGNETIK PASIR BESI BERBASIS SENSOR FLUXGATE - Febri Nanda (PILLAR OF PHYSICS, 2013)
Measurement of magnetic fields is important because many objects are magnetic and rewarding life. One thing that is both magnetic and used in this study were iron sand. To measure the magnetic field of an object fluxgate sensor is needed to detect the magnetic field. Fluxgate sensor is a magnetic sensor that works based on changes in the magnetic flux around the sensor element. The purpose of this study is to explain the function of each part of the gauge and determine the linearity and accuracy of the measuring instrument. Measuring instrument fluxgate magnetic field sensor based consists of two essential parts, namely the elements of the fluxgate sensor and its supporting series consisting of power supply circuit, signal processing circuit, and a microcontroller circuit. After the measurements are obtained linearity of the current magnetic field in the solenoid is 0.990. While the accuracy of the tool through a calculation 0.998. This instrument has linearity and accuracy are high enough to the magnetic field. Keywords        : magnetic field, fluxgate sensor, iron sands